Acquired methemoglobinemia: A systematic review of reported cases. (April 2022) - Gao, Haijuan; Basri, Rabia; Tran, Minh-Ha
Abstract: Introduction: Acquired methemoglobinemia may cause cyanosis and tissue ischemia unresponsive to oxygen supplementation. Methods: We performed a literature search to identify cases of acquired methemoglobinemia published between 1980 and 2020. Clinical, diagnostic, and treatment details were extracted from eligible cases. Results: A total of 76 reports involving 87 cases were analyzed. The median age at presentation was 32.5 with male to female ratio of 1.6. Cyanosis and SpO2 <90 % were reported in 82 % and 60 % of cases, respectively. Dapsone or cocaine-based anesthetics were causative in 52 % of cases; most anesthetic-related cases occurred in the peri-procedural setting. Methylene blue (MB) and red cell transfusion were given in 71 % and 10 % of cases, respectively. Compared to MB untreated patients, MB treated patients were more likely to be cyanotic (91.9 % vs 54.2 %), had higher proportions (%) and levels (g/dL) of methemoglobin (MetHb) – 33.2 % vs 15.3 % and 3.1 g/dL vs 1.2 g/dL, respectively. We found that among cyanotic cases, the median MetHb level was 3.0 g/dL (0.4–12.3 g/dL) with 74 % of values ≥ 1.5 g/dL. An SaO2:SpO2 ratio of >1 was not universally present, but always coincided with an [SaO2 -SpO2 ] delta value greater than zero. Conclusions: Cyanosis and hypoxemia were not universal findings of acquired methemoglobinemia in our series. In addition, not all patients had cyanosis at MetHb ≥ 1.5 g/dL or an SaO2:SpO2 ratio of >1. All those with an SaO2 :SpO2 >1 did, however, have a delta value greater than zero – a finding not previously reported which we feel holds diagnostic value.